POLYCYCLIC AROMATIC HYDROCARBONS AS A LIMITING PARAMETERS OF TRADITIONAL PRODUCTION OF DRY-CURED MEAT PRODUCTS - Vranešević, Jelena; Vidaković Knežević, Suzana; Kartalović, Brankica; Škaljac, Snežana; Plavša, Nada; Mastanjević, Krešimir; Novakov, Nikolina (Food and Feed Research, 2024)
The goal of the study was to investigate the concentration of 16 US EPA polycyclic aromatic hydrocarbons (PAHs) and check the sensory properties in 11 dry-cured meat products, smoked in three different ways (atmospheric simulation chamber (ATMOS), industrial chamber and traditional craft smokehouse) in one meat industry facility in Serbia. Controlled industrial production cannot provide all distinguishable and specific sensory properties of traditional dry-cured products, so more and more frequently meat industries decide to include the products smoked in traditional craft smokehouses in their product assortment. 16 US EPA PAHs were determined using a gas chromatography-mass spectrometry method (GC-MS). The obtained results are part of the production technology validating process of the tested smoked meat products. Total concentrations of benzo(a)pyrene, benzo(a)anthracene, benzo(b)fluranthene and chrysene (comprising the so-called “PAH4” group) in traditional homemade smoked bacon produced in compliance with all the guidelines of good manufacturing and hygiene practice, reached 15.82 µg/kg what was above the legal limits set by Serbian legislation. This indicates that there is a need for monitoring the PAH content compounds in traditional smoked meat products, and quite likely the revision of the current rulebook on traditional dry-cured meat products following the EU practice.
Keywords: PAHs; meat products; traditional production; ATMOS